Seasonal stem growth analysis shows early stem growth of Miscanthus from high latitudes yields more biomass but stem traits negatively interact to limit seasonal growth - Robson, Paul R. H.; Hawkins, Sarah; Davey, Christopher L.; Clifton-Brown, John C.; Slavov, Gancho (Frontiers in Plant Science, 2025)
High yielding perennial grasses are utilised as biomass for the bioeconomy and to displace fossil fuels. Miscanthus is a perennial grass used as a source of biomass but most of the cultivated crop is limited to a naturally occurring hybrid M. × giganteus. Miscanthus species originate from an extensive latitudinal and longitudinal range across Asia and thus have considerable potential to diversify the crop and improve yield. In previous studies stem morphological traits correlated strongly with yield in Miscanthus but little is known about how the development of stem growth may be optimised across the growth season. The aims of this study are to identify strategies to optimise seasonal growth duration and improve yield. To do this yield and seasonal stem elongation were measured from large numbers of diverse genotypes and functional data analysis used to characterise and compare the diverse perennial stem growth strategies. A diversity trial of over 900 genotypes was established in three replicates in the field at Aberystwyth, UK. Stem elongation was measured across the entire season for 3 consecutive years and the Richards growth function was fitted to model growth. Differentials, double differentials and integrals of the parameterised functions produced six growth characteristics, describing the growth rate, the timing and duration of the logarithmic growth phase and the integral of stem growth. Plants were also assessed for yield and moisture content. Growth traits from all plants in the diversity trial were moderately correlated, were correlated with biomass moisture content but less so to accumulated dry weight of biomass. Plants that grew for longer tended to have lower growth rates, but individual exceptions were identified. Plants with a similar duration of logarithmic growth achieved greater growth rates and harvestable yield if growth began earlier in the season and early season growth was mostly explained by latitude and altitude from which the accessions were collected. Stem growth traits were highly heritable and there was a significant effect of species on all growth characteristics. We discuss the possible interactions between growth and developmental control in perennials that may be exploited to improve yield in these crops.